Pemikiran M. Amin Abdullah tentang Pendidikan Islam dalam Pendekatan Integrasi-Interkoneksi - Abdullah Diu (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2018)
The dynamics of Islamic education in Indonesia shows a dichotomy, both Islamic education and general education. Islamic education is often named only for the benefit of those who are poor or poor, produce exclusive, fanatical people, and even at a very sad level, terrorism is considered to be from Islamic education institutions. This is called the marginalization of Islamic education. Besides that the quality of Islamic education is called very underdeveloped or lacking in quality. M. Amin Abdullah's view of Islamic education in the integration-interconnection approach breaks down the basis of the approach, namely the historical-philosophical, normative-theological approach. Having a very clear root in the world of science the position of Islamic education includes hadlarah al-nash, hadlarah al-‘ilm, and hadlarah al-falsafah is an effort to reconnect between Islamic sciences and general sciences.